A strategy of ideotype development for heat‐tolerant wheat. (29th November 2019) - Ullah, Smi; Bramley, Helen; Mahmood, Tariq; Trethowan, Richard
Abstract: Heat stress significantly limits yield in many wheat‐growing areas globally including north‐western NSW. While various traits linked to high‐temperature tolerance have been identified, the combination of traits that optimize the heat tolerance of wheat has not been established in most environments. A total of 554 genotypes were evaluated in the field at different times of sowing in north‐western NSW for three consecutive years to develop a heat‐tolerant wheat ideotype for this environment. The later sown experiments were exposed to higher temperatures at the critical reproductive and grain‐filling stages of development. The impact of high temperature was greatest at anthesis, and eventual grain yield was reduced by between 4% and 7% with every 1°C rise in average maximum temperature above the optimum of 25°C. High temperature reduced yield, plant height, grain weight and days to anthesis and maturity, and increased the percentage of screenings and grain protein content. Genotypes that produced higher yield under heat stress had shorter days to flowering and maturity, higher NDVI during grain filling, greater chlorophyll content at the milk stage of grain fill, taller plants, greater grain weight and number, and lower screenings compared with the benchmark cultivar Suntop. The genotype closest to the predicted heat‐tolerant wheat ideotype identified from trait ranges had 79.6% similarity.